2016
DOI: 10.1242/jcs.185595
|View full text |Cite
|
Sign up to set email alerts
|

The Src kinases Hck, Fgr, and Lyn activate Abl2/Arg to facilitate IgG-mediated phagocytosis andLeishmaniainfection

Abstract: Leishmaniasis is a devastating disease that disfigures or kills nearly two million people each year. Establishment and persistence of infection by the obligate intracellular parasite Leishmania requires repeated uptake by macrophages and other phagocytes. Therefore, preventing uptake could be a novel therapeutic strategy for leishmaniasis. Amastigotes, the life cycle stage found in the human host, bind Fc receptors and enter macrophages primarily through immunoglobulin-mediated phagocytosis. However, the host … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(98 citation statements)
references
References 89 publications
(118 reference statements)
5
91
1
Order By: Relevance
“…Wetzel et al . demonstrated that a tyrosine kinase non-receptor known as Abl2 facilitates L. amazonensis amastigote uptake by macrophages 34 . Once inside the phagolysosomes, promastigotes differentiate into amastigotes and proliferate extensively by binary fission, evading the immune response.…”
Section: Etiopathogenesismentioning
confidence: 99%
“…Wetzel et al . demonstrated that a tyrosine kinase non-receptor known as Abl2 facilitates L. amazonensis amastigote uptake by macrophages 34 . Once inside the phagolysosomes, promastigotes differentiate into amastigotes and proliferate extensively by binary fission, evading the immune response.…”
Section: Etiopathogenesismentioning
confidence: 99%
“…SFKs appear to be exclusively involved in "outside-in" signaling, as SFK-deficient cells produced reduced ROS after integrin clustering (113), whereas ICAM-1 adhesion and complement-dependent phagocytosis were normal in preactivated SFK-deficient cells (114,115).…”
Section: Clustering and Tyrosine Kinasesmentioning
confidence: 99%
“…Bosutinib (Figure ), an Abl and Src kinase inhibitor, is an antineoplastic drug approved for CML and other cancers . Bosutinib inhibited L. amazonensis promastigote and amastigote uptake by bone marrow‐derived macrophages (BMDMs) of 49 and 46 %, respectively . In the same work, it has been shown that bosutinib reduces the lesion size in a mouse model of CL.…”
Section: Human Kinase Inhibitor Repurposing In Trypanosomatidsmentioning
confidence: 88%